PENGARUH RIGHT ISSUE TERHADAP RETURN SAHAM DI JAKARTA STOCK EXCHANGE SEBELUM DAN SELAMA MASA KRISIS EKONOMI 1997 - Djoko Hanantijo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Companies that already gone public can conduct a limited public offering (right issues) if you want to add funds. This is achieved so that the risk of corporate debt can be lowered, and can increase stock returns. This study aims to determine the influence of the use of proceeds from the rights issue to the return earned by shareholders priors to the economic crisis compared during the economic crisis. The research data was obtained from company documents right issue at the Jakarta Stock Exchange (JSX) in 1996 – 1998, with a total sample of 18 companies that the right issue in 1996 – 1998. The sample taken is a company that was preceded by rights issues without warrants, convertible bond or share dividend. Each industry group represented only one company only by relying on the most activity. Then the samples were grouped into 14 companies that the rights issue before the economic crisis and the four companies that the right issues during the economic crisis. The result showed that the average return of the stock before the company’s right issues has increased during the economic than before the economic crisis. While the average return of the stock after the company’s rights issue was not increased during the economic crisis than before the economic crisis.Keywords: go public, the rights issue, stock return, economic crisis